STRATEGI KREATIF DAN PROSES PEMBUATAN PROGRAM TELEVISI - Tri Wahyuti (Program Studi Ilmu Komunikasi Universitas Paramadina, 2015)
One of factors in determining success of a television program is the creativity that made by the programmer. Non-news or entertainment programs require creativity from pre-production to post-production stage . This article will explain the strategy that should be done by the programmer in making creative and entertainment tv program. The strategy of making a television program is divided into four strategies: making ideas, positioning, implementing and evaluating. This paper will also provide examples of successful tv program which has been televised in Indonesia . Key words: program, tv, creative strategy, entertainment, idea, positioning, implementation, evaluation.